Liver Disease in Diabetes Mellitus: Potential Therapeutic Value of Vitamin E-Silybin Phytosomal Complex - Matteucci, Elena; Chiara Masoni, Maria; Consani, Cristina; Giampietro, Ottavio (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2010)
The liver has a central role in glucose homeostasis. In turn, glucose-induced signals modulate the transcriptional regulation of genes involved in the glycolysis and lipogenesis pathways and could favour fatty acid storage in the liver. The prevalence of hepatobiliary diseases is increased in patients with diabetes mellitus. Type 1 diabetes is associated with a hepatic form of microvascular disease (diabetic hepatosclerosis), hemochromatosis and autoimmune hepatitis. Type 2 diabetes is associated with nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) whose prevalence increases with multiple components of metabolic syndrome. Hepatitis C virus infection has been reported to be associated with and predispose to diabetes mellitus. Silibinin or silybin is a flavonoid derived from Silybum marianum and known to have hepatoprotective, anti-carcinogenic and anti-inflammatory effects. Silymarin is a standardised extract of four polyphenolic flavanolignans (silybin, isosilybin, silydianin and silychristin) from the seeds of Silybum marianum; it possesses a potent scavenging capacity of oxidizing free radicals whose mechanistic aspects have been extensively evaluated. This single herbal drug formulation is used for hepatoprotection although recent evidence in carbon tetrachloride- induced cirrhotic rats suggests that chronic silymarin treatment might compromise the hemodynamic endothelial nitric oxide synthase activity. In order to enhance silymarin bioavailability flavonoid molecules have been converted into lipid-compatible molecular complexes, phytosomes. A new silybin-phosphatidylcholine-Vitamin E complex, characterised by elevated oral bioavailability and lipophilicity, was effective on rat hepatic fibrosis induced by dimethylnitrosamine administration and by bile duct ligation. The complex has been suggested as a complementary approach to the treatment of patients with chronic liver damage. The manuscript provides a review of literature on this topic and discusses the potential usefulness of the complex to prevent/treats liver disease in diabetes as well as contraindications.
Keywords: isosilybin